Analisis Pengaruh Sistem Eksitasi Terhadap Tegangan Keluaran Generator Sinkron Mini Hydro - Dede Furqon Nurjaman (Department of Electrical Engineering, UNJANI, 2021)
Dynamic loading or changing at any time will have an impact on the generator, one of the effects is the change in the generator terminal voltage. So that every generator that contributes to the interconnection system is required to be ready to face any system changes. The purpose of this research is to determine the effect of the excitation current on the generator voltage. In this study, the data obtained were carried out by direct observation, namely by taking the required data and carrying out experimental methods by conducting several experiments in obtaining data, such as operating a generator and to get the value of the generator loading to be analyzed. with the measurement method. The results indicate that the voltage of the synchronous generator Mini Hydro Curug is strongly influenced by the size of the excitation current setting, this can be seen at the time of loading the generator, when the excitation current is 2.2 A, the generator output voltage value is 6.133 kV. , and the highest generator output voltage is at a value of 6.479 kV with an excitation current of 4.6 A.